Role of M3 Muscarinic Acethylcholine Receptor Antibodies as a New Marker in Primary Sjögren Syndrome - Reina, Silvia Lorena (2017)
Aims: This paper investigates the presence of M3 muscarinic acetylcholine receptor autoantibody present in the serum of patients with primary Sjögren syndrome (pSS). Main methods: We detected the levels of M3mAChR peptide IgG, PGE2, IL-1β in serum of SS patients using the enzyme-linked immune sorbent assay (ELISA). To measure the quantity of nitrite/nitrate, we used Griess reagent system. Key findings: Titres of M3mAChR antibody in sera from SS patients are significantly enhanced compared to healthy subjects (control). The enhancement of these autoantibodies is accompanied by the increase of the levels of PGE2, IL-1β and nitrite/nitrate in serum. Under in vitro conditions, the synthetic human M3 peptide impaires the increment of M3mAChR antibody but not that of nati-Ro/SSA antibody. In positive anti-Ro/SSA antibody patients, the increment of M3mAChR peptide IgG and the measured pro-inflammatory substances is related. Significance: On this basis, anti M3mAChR peptide IgG can be said to act as a modulator of the immune system and to play a role in the host-chronic increment of proinflammatory substances in SS patients with positive Ro/SSA antibody. This association between the antibody and the pathogenesis of SS disease may result in useful predicting SS.